Pengaruh Locus Of Control dan Tekanan Anggaran Waktu terhadap Perilaku Disfungsional Auditor: Studi Empiris pada Kantor Akuntan Publik di Kota Padang - Putri Rahmawati; Halmawati Halmawati (Wahana Riset Akuntansi, 2020)
This study aims to examine the effect of locus of control and time budget pressure on the auditor's dysfunctional behavior. The population in this study are all public accounting firms in the city of Padang, using a total sampling method, there are 8 public accounting firms that can be used as research samples and collected as many as 47 questionnaires. Data analysis methods used in this study was multiple linear regression analysis. The results of this study support the second and third hypotheses, internal locus of control has a negative influence on the auditor's dysfunctional behavior and budget time pressure has a positive influence on the auditor's dysfunctional behavior. However the results of this study reject the first hypothesis that external locus of control does not have a positive and significant effect on the dysfunctional behavior of auditors working in public accounting firms in the city of Padang.Keywords: Auditor's Dysfunctional Behavior; External Locus of Control; Internal Locus of Control; Time Budget Pressure.